PENGARUH PENERAPAN SMKK TERHADAP PENGENDALIAN RISIKO PEKERJAAN STRUKTUR ATAS JEMBATAN - Amalia Fitriani; Kusumo Dradjad; Jonathan Saputra (Politeknik Negeri Jakarta, 2022)
An important step toward preventing work accidents on construction projects is the implementation of Sistem Manajemen Keselamatan Konstruksi (SMKK). According to Peraturan Menteri PUPR No. 10 Tahun 2021, The X Highway is a project with a high safety risk rating. This study examines how SMKK elements are applied and how that application influences risk management during bridge upper structural work. Examining documents, conducting interviews, and distributing questionnaires are all examples of data collection techniques. The first analysis involved determining whether each document was appropriate for each element before dividing the number of indicators attained by the total number of indicators. The SPSS application was used to carry out statistical computations for the second analysis. According to the findings, the X highway Project has an average value of 92% of the SMKK implementation rate, indicating a satisfactory application rate.From the results of hypothesis tests on the application of SMKK elements to risk control, of the five SMKK element variables, three SMKK elements partially have a significant effect, and simultaneously, the SMKK element variables have a significant effect. The results of the projection of the multiple linear regression equation on the value of the level of application of the SMKK element show that the Perencanaan Keselamatan Konstruksi and Operasi Keselamatan Konstruksi elements have a low value of risk control influence compared to other SMKK elements. So, it has a higher possibility that these elements will be a source of risk to the upper structure work of the X Highway Project. Keywords: Risk of Control, SMKK, Upperstructure of the Bridge.